Reproductive disorders in Portuguese Serrana goats and its effects on milk production - Simões, João; Pires, Alda F. A. (Revista Colombiana de Ciencias Pecuarias, 2018)
Background: Abortions and parturitions with stillbirths are frequent in goat herds. However, the incidence of these events should remain low and their effects on subsequent lactation need to be assessed at breed level. Objective: To evaluate the incidence of abortions and parturitions with stillbirths (APS) in Portuguese Serrana goats breed ecotype Transmontano, and their association with milk production in subsequent lactation. Methods: Records of Serrana goats ecotype Transmontano from the pedigree book between 1997 and 2014 were used in order to determine the occurrence of APS. Goat level information, such as normal parturition and/or APS dates, number of fetuses, parity, and 150-d normalized milk production for each subsequent lactation, was considered. Results: The average incidence of APS was 8.7% (19,351/223,798). According to a multivariable logistic analysis, the year, month, parity, gemelarity, and their interactions were factors significantly (p < 0.001) associated with APS. In overall, a higher APS incidence was observed in single births and primiparous goats. The 150-d normalized milk production was lower (p < 0.001) in the APS group than in goats with normal parturitions. Conclusion: The APS incidence in Serrana goats ecotype Transmontano was higher than other ruminants, and APS had a negative effect on milk production considering the 150-d normalized lactation.